Peningkatan Produktivitas Padi Gogo (Oryza Sativa Linnaeus) Akibat Aplikasi Pupuk Urea Dan Bakteri Pemfiksasi Nitrogen Dalam Bahan Pembawa Pada Inceptisols Asal Jatinangor - Fadhilla Oktavianingtyas Trisilvi; Nadia Nuraniya Kamaluddin; Betty Natalie Fitriatin; Diyan Herdiyantoro; Pujawati Suryatmana (Fakultas Pertanian Universitas Padjadjaran, 2021)
As a staple in Indonesian diet, rice demand increase along with the population growth. Therefore, in order to fulfill the continuous increase, researches were conducted to increase land productivity. The increase of growth and productivity of upland rice with the application of Azospirillum sp. and Azotobacter sp. in compost, Azolla, and rice bran carrier were studied. Nitrogen fixer were applied as a biofertiliser as a mean to supply available nitrogen for upland rice growth. This research was conducted in Ciparanje Experimental Field and Soil Biology Laboratory, Faculty of Agriculture, Universitas Padjadjaran. In this research, Randomized Block Design was used to analyze two factors: urea dose (100% and 50%) and Nfixer bacteria in various carriers (individual carrier and combination of liquid inoculant, green compost, Azolla compost, rice bran). The result showed an interaction between two factors towards the grain weight of upland rice. The application of 100% urea dose showed higher result compared to 50% urea dose on grain weight. N fixer bacteria combined with compost, Azolla, and rice bran carrier gave the highest result on the number of tillers, chlorophyll content, and grain weight.